2021
DOI: 10.1108/jpbm-09-2020-3126
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the antecedents to luxury brand consumer behavior

Abstract: Purpose This paper aims to investigate how consumers perceive the value of luxury brands and the antecedents to these perceptions, including consumer knowledge, reference group influence and accessibility. Prior studies focused less on the salience of consumer knowledge and sources of luxury information, in addition to their accessibility to luxury. Hence, a more nuanced luxury conceptualization is needed to reflect luxury’s conceptual fluidity, consumers’ different lived experiences, accessibility levels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 64 publications
0
11
0
1
Order By: Relevance
“…Reference group influence is positively related to luxury value perceptions for a consumer's favorite luxury brand (Kowalczyk and Mitchell, 2021). It is important to note that what consumers perceive to be luxury ranged from traditional luxury to masstige to nontraditional luxury brands (Kowalczyk and Mitchell, 2021;Shin et al, 2021). Das et al (2021) found that interpersonal influence moderated the relationship between need for uniqueness and inspiration for masstige.…”
Section: Role Of Interpersonal Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Reference group influence is positively related to luxury value perceptions for a consumer's favorite luxury brand (Kowalczyk and Mitchell, 2021). It is important to note that what consumers perceive to be luxury ranged from traditional luxury to masstige to nontraditional luxury brands (Kowalczyk and Mitchell, 2021;Shin et al, 2021). Das et al (2021) found that interpersonal influence moderated the relationship between need for uniqueness and inspiration for masstige.…”
Section: Role Of Interpersonal Influencementioning
confidence: 99%
“…As luxury goods are perceived to be the most visible form of consumption (Vigneron and Johnson, 2004), interpersonal influence plays a key role. Reference group influence is positively related to luxury value perceptions for a consumer's favorite luxury brand (Kowalczyk and Mitchell, 2021). It is important to note that what consumers perceive to be luxury ranged from traditional luxury to masstige to nontraditional luxury brands (Kowalczyk and Mitchell, 2021;Shin et al, 2021).…”
Section: Role Of Interpersonal Influencementioning
confidence: 99%
“…Brand image researchers recognize that associations are often based on personal preferences, emotions and values (Anselmsson et al , 2007; French and Smith, 2013; Keller, 1993), and luxury brand researchers increasingly acknowledge the critical role of consumers’ personal values in guiding their purchase decisions (Atkinson and Kang, 2021; Kauppinen-Räisänen et al , 2019; Kowalczyk and Mitchell, 2021), but research that explains the role of consumers’ values in the emergence of a brand image seems to be missing. The next section offers such an explanation.…”
Section: A Conceptual Framework For the Emergence Of A Values-based P...mentioning
confidence: 99%
“…Reference group is a person or group (society) that influences consumer behavior (Kowalczyk & Mitchell, 2022;Preiksaitis & Dacin, 2021). According to Liljedal & Berg, (2020) and Preiksaitis & Dacin, (2021) reference group is a group that has a certain view of how to act in a situation.…”
Section: References Groupmentioning
confidence: 99%
“…Types of reference groups according to Sumarwan (2014:306) concluded that the types of reference groups are divided into three, namely formal and informal groups, primary and secondary groups, and aspiration and dissociation groups. Meanwhile, the reference/reference groups based on their grouping are divided into 3 (three) namely groups based on proximity and intensity of interaction, groups based on the legality of existence, and groups based on membership status and influence (Kennedy et al, 2022;Kowalczyk & Mitchell, 2022;Preiksaitis & Dacin, 2021). Reference groups / reference groups that influence consumers in essence can provide information, experience, credibility, attractiveness, strength of the reference group and product prominence (Dalman et al, 2020;Kaur et al, 2020).…”
Section: References Groupmentioning
confidence: 99%